Pengaruh Penggunaan Model Project Based Learning (PJBL) Terhadap Pemahaman Konsep Pada Materi Pengukuran Sudut Di Kelas IV SD - Rahmi Yunisa Malta; Melva Zainil (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to determine the effect of Project Based Learning on the concept of understanding on the angle measurement material in the fourth grade of Kenagarian Tanjung Sani Maninjau elementary school. The form of this research design is a quasi experimental research design type of non equivalent control design. The sample in this study was class IV SDN 17 Pandan and Class IV SDN 15 Tanjung Sani. The results of the calculation of the research used were the t-test obtained t count> t table (2.97> 1.684) at the α 0.05 level. Thus it can be concluded that there is an influence of the PPA approach to the understanding of concepts in the angle measurement material in the fourth grade of SD Sagran Maninjau Kenagarian Group.